Association between Antifibrinolytic Therapy and Perioperative Outcomes in Patients with Coronary Artery Stents Undergoing Noncardiac Surgery - Boswell, Michael R. (Anesth Analg, 2021)
BACKGROUND: Patients with existing coronary artery stents are at increased risk for major adverse cardiac events (MACE) when undergoing noncardiac surgery (NCS). Although the use of antifibrinolytic (AF) therapy in NCS has significantly increased in the past decade, the relationship between perioperative AF use and its association MACE among patients with existing coronary artery stents has yet to be assessed. In this study, we aim to evaluate the association of MACE in patients with existing coronary artery stents who receive perioperative AF therapy during orthopedic surgery. METHODS: A single-center retrospective cohort study was conducted in adult patients with existing coronary artery stents who underwent orthopedic surgery from 2008–2018. Two cohorts were established: patients with existing coronary artery stents who did not receive perioperative AF and patients with coronary artery stents who received perioperative AF. Associations between AF use and the primary outcome of MACE within 30-days postoperatively and the secondary outcomes of thrombotic complications, excessive surgical bleeding, and ICU admissions were analyzed using logistic regression models. Inverse probability of treatment weighting was used to control for confounding. Secondary analyses examining the association between coronary stent type/timing and the outcomes of interest were performed using unadjusted logistic regression models. RESULTS: 473 patients met study criteria, including 294 who did not receive AF and 179 patients who received AF. MACE occurred in 15 (5.1%) patients who did not receive AF and 1 (0.6%) who received AF (p=0.007). In weighted analyses, no significant difference was found in patients who received AF with regard to MACE (OR 0.13, 95% CI=0.01–1.74, p=0.12), thrombotic complications (OR 1.19, 95% CI=0.53–2.68, p=0.68), or excessive surgical bleeding (OR 0.13, 95% CI=0.01–2.23, p=0.16) compared to patients who did not receive AF. CONCLUSION: The results of this study are inconclusive whether an association exists between perioperative AF use in patients with coronary artery stents and the outcome of MACE compared to patients who did not receive perioperative AF therapy. The authors acknowledge that the imprecise confidence interval hinders the ability definitively determine whether an association exists in the study population. Further large prospective studies, powered to detect differences in MACE, are needed to assess the safety of perioperative AF in patients with existing coronary artery stents and to clarify the mechanism of perioperative MACE in this high-risk population.